A Study of Problems and Solutions of Teacher Education in India - Dharmisthaben Ramanbhai Chauhan (AG Volumes, 2022)
Education makes a substantial contribution to the successful growth and development of persons, and instructors have a crucial role to play in the process of providing pupils with education. The primary emphasis of the relevance of teacher education should be on the training that should be provided to teachers, with the overarching objective being the accomplishment of the desired scholastic results. Teachers play a crucial part in fostering their students' personal and intellectual development. Accordingly, it is crucial for them to improve their skills and talents in order to accomplish their work obligations to the appropriate quality. A teacher's contribution is crucial not just to the success of the school as a whole but also to the greater good of the community. A lot of difficulties will arise when they carry out their tasks for the company. This research study focuses primarily on three key areas: the first is the scope of teacher education; the second is the shifting context of teacher education in the Indian scenario; and the third is the issues that face teacher education.